PENGARUH PENDAPATAN ASLI DAERAH, DANA BAGI HASIL PAJAK, DAN DANA BAGI HASIL BUKAN PAJAK TERHADAP DANA ALOKASI UMUM KABUPATEN DAN KOTA DI PROVINSI KEPULAUAN BANGKA BELITUNG - Mona Patrecia Sinambela; Abu Nizarudin; Muhammad Qomaruddin Ridwan (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2026)
The General Allocation Fund (Dana Alokasi Umum/DAU) serves as a strategic instrument for supporting regional autonomy and promoting fiscal equity across regions. However, the amount of DAU a region receives is heavily influenced by its fiscal capacity, as reflected in Local Revenue (PAD), Tax Revenue Sharing Funds (DBHP), and Non-Tax Revenue Sharing Funds (DBHBP). These three components determine the fiscal gap underlying DAU calculations, making it essential to empirically understand their influence. This study aims to examine and analyze the effect of PAD, DBHP, and DBHBP on DAU across regencies and cities in Bangka Belitung Islands Province. Using a quantitative approach, the study processes secondary data from the 2014–2023 regional budget realization reports (APBD), obtained from the Directorate General of Fiscal Balance, and analyzed using multiple linear regression. The results show that PAD, DBHP, and DBHBP each exert a negative effect on DAU, meaning that higher fiscal capacity leads to lower DAU allocations from the central government. These findings imply that the central government should refine the DAU allocation formula to better reflect fiscal fairness, while regional governments should be encouraged to optimize own-source revenues without being disincentivized by disproportionate reductions in DAU transfers.